Multi-disciplinary approaches paving the way for clinically effective peptide vaccines for cancer - Bansari A. Shah; James A. Holden; Jason C. Lenzo; Sara Hadjigol; Neil M. O’Brien-Simpson (npj Vaccines)
Abstract Cytotoxic CD8+ T lymphocyte (CTL) cells are central in mediating antitumor immunity. Induction of a robust CTL response requires, CTL interaction with professional antigen-presenting cells, such as dendritic cells, displaying onco-antigenic peptide, often derived from tumor-associated antigens (TAAs) or neoantigens, and costimulation via CD4+ T helper cells which then elicits an effector and memory immune response that targets and kills cancer cells. Despite the tumoricidal capacity of CTLs, cancer cells can escape immune surveillance and killing due to their immunosuppressive tumor microenvironment (TME). Therefore, to harness the CTL immune response and combat the effect of the TME, peptide-based T cell vaccines targeting specific onco-antigens, conjugated with adjuvants are a subject of ongoing research for cancer immunotherapy; particularly, multi-peptide vaccines, containing both CTL and CD4+ T helper cell epitopes along with an immunostimulant. Historically, peptide-based T cell vaccines have been investigated as a potential strategy for cancer immunotherapy. Despite initial enthusiasm, these peptide vaccines have not demonstrated success in clinical outcomes. However, recent advancements in our understanding of cancer immunology and the design of peptide vaccines targeting specific tumor antigens have paved the way for novel strategies in peptide-based immunotherapy. These advancements have reignited optimism surrounding the potential of peptide-based vaccines as a viable cancer therapeutic. This review explores the new strategies and discusses the exciting possibilities they offer. Specifically, this review develops an understanding of vaccine design and clinical outcomes, by discussing mechanisms of CTL effector and memory responses, and how peptide-based vaccines can induce and enhance these responses. It addresses the challenge of Major Histocompatibility Complex (MHC) restriction, which limits the effectiveness of traditional peptide vaccines in individuals with diverse MHC types. It also delves into the immunosuppressive tumor microenvironment and overcoming its inhibitory effects using peptide-based vaccines for efficient cancer cell elimination. The review aims to provide an understanding of the complexities faced by each field in vaccine design, enhancing dialogue and understanding among researchers by bringing together the chemistry of vaccine synthesis, cancer immunology, and clinical studies to support the development of a peptide-based vaccine.